2021
DOI: 10.21037/tcr-21-1034
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of retinoblastoma pathogenesis with bioinformatics

Abstract: Background: Differentially expressed genes (DEGs) from retinoblastoma (RB) tissues play key roles in the progression of RB. However, the role of DEGs in different subtypes and stages of RB has not yet been systematically analyzed.Methods: In this study, the DEGs for tumor and adjacent from 3 RB data sets GSE24673, GSE97508, and GSE110811 were analyzed with regard to the different subtypes and stages of the disease.Results: Through comparison with adjacent tissues, a total of 78 upregulated genes and 155 downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Previous microarray and bioinformatics analysis on RB tumor specimens revealed that the above enriched terms were associated with RB tumor occurrence, development, and chemo-resistance by regulating cell growth, cell survival, and proliferation. 22 , 29 , 30 Several studies have demonstrated that the neuroactive ligand–receptor interaction pathway is linked to a poor prognosis in various cancers, and breast cancer patients with low expression of cannabinoid receptor 1 (CNR1, part of this pathway) may benefit from chemotherapy. 31 Bioinformatics analysis of gene expression data of RB tumor tissues compared to normal retina revealed that the aberrantly expressed protein coding genes and target genes for DE lncRNAs are enriched for neuroactive ligand–receptor interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous microarray and bioinformatics analysis on RB tumor specimens revealed that the above enriched terms were associated with RB tumor occurrence, development, and chemo-resistance by regulating cell growth, cell survival, and proliferation. 22 , 29 , 30 Several studies have demonstrated that the neuroactive ligand–receptor interaction pathway is linked to a poor prognosis in various cancers, and breast cancer patients with low expression of cannabinoid receptor 1 (CNR1, part of this pathway) may benefit from chemotherapy. 31 Bioinformatics analysis of gene expression data of RB tumor tissues compared to normal retina revealed that the aberrantly expressed protein coding genes and target genes for DE lncRNAs are enriched for neuroactive ligand–receptor interaction.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Bioinformatics analysis of gene expression data of RB tumor tissues compared to normal retina revealed that the aberrantly expressed protein coding genes and target genes for DE lncRNAs are enriched for neuroactive ligand–receptor interaction. 29 , 30 Moreover, this is one of the 50 pathways significantly enriched for DEGs between chemoresistance Y79 versus parental Y79 cells. 32 MicroRNAs in cancer were enriched only for DE genes of TR-RB.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports have described the upregulation of UHRF1 in cancer cells (Table 1 ). 99 106 ) Because higher expression is often correlated with more advanced cancer stages, multiple metastases, and/or poor prognosis, UHRF1 has been suggested as a good biomarker for various malignancies. 99 ) In addition, because UHRF1 expression is limited to proliferating cells, inhibitors of UHRF1 may be ideal candidates for anticancer drugs that could act across a broad spectrum of cancer types, with minimal adverse effects.…”
Section: Dysregulation Of the Uhrf Protein Family In Cancermentioning
confidence: 99%